Wind Tunnel Testing of Yaw by Individual Pitch Control Applied to Wake Steering - Campagnolo, Filippo; Castellani, Francesco; Natili, Francesco; Astolfi, Davide; Mühle, Franz (Frontiers in Energy Research, 2022)
The yaw control of horizontal-axis wind turbines is the key point for wake redirection, which is expected to provide an improvement in the balance between wind farm production and loads. For multi-MW upwind wind turbines, there are substantially two possibilities for obtaining a desired demanded yaw angle: using yaw actuators or Individual Pitch Control (IPC). A detailed balance of the pros and cons of both approaches requires in-depth studies. On these grounds, this work is a comprehensive experimental characterization of the yaw by individual pitch control (yaw-by-IPC). The experiments are conducted at the R. Balli wind tunnel of the University of Perugia on a fully instrumented wind turbine scaled model, named G1, developed by the Technical University of Munich. The objective of the study is twofold: assessment of the performance of the yaw-by-IPC in terms of yaw tracking capabilities and impact on power, loads, and actuators usage; analysis of its impact on the shed wake. The wake has been characterized on a plane parallel to the rotor at a distance of 1.82 diameters by imposing several steady yaw references, while wind intensity measurements have been performed through a traversing system hosting a hot wire anemometer. Each target of the analysis has been characterized for the yaw-by-IPC and for the control based on yaw actuation, in order to perform a comparison. With laminar inflow, it results that the yaw-by-IPC follows very well the demanded reference, even with a slight improvement in the case of dynamic yaw reference, and no power losses are visible. Concerning the wake shed by a yawed G1 with yaw-by-IPC, a higher flow speed is observed immediately behind the windward side of the rotor than with geared yaw actuation. It results, therefore, that yaw-by-IPC applied to a yawed wind turbine may increase the available wind power at a downstream machine.